Volatile Organic Compounds in Blood as Biomarkers of Exposure to JP-8 Jet Fuel Among US Air Force Personnel. Issue 1 (January 2016) - Maule, Alexis L.; Proctor, Susan P.; Blount, Benjamin C.; Chambers, David M.; McClean, Michael D.
Abstract : Objective: This study aimed to evaluate blood volatile organic compound (VOC) levels as biomarkers of occupational jet propulsion fuel 8 (JP-8) exposure while controlling for smoking. Methods: Among 69 Air Force personnel, post-shift blood samples were analyzed for components of JP-8, including ethylbenzene, toluene, o -xylene, and m/p -xylene, and for the smoking biomarker, 2, 5-dimethylfuran. JP-8 exposure was characterized based on self-report and measured work shift levels of total hydrocarbons in personal air. Multivariate regression was used to evaluate the relationship between JP-8 exposure and post-shift blood VOCs while controlling for potential confounding from smoking. Results: Blood VOC concentrations were higher among US Air Force personnel who reported JP-8 exposure and work shift smoking. Breathing zone total hydrocarbons was a significant predictor of VOC blood levels, after controlling for smoking. Conclusions: These findings support the use of blood VOCs as a biomarker of occupational JP-8 exposure.